Sítio arqueológico Ruínas da Estância Santa Clara: uma unidade doméstica da fronteira oeste/RS - Pes, Jaqueline Ferreira (2013)
This paper aims to present research carried out at the historical Ruínas da Estância Santa Clara archaeological site, a place located in the rural area of Quaraí / RS, in the Artigas and Uruguay border. The field interventions were done in 2009 and 2011, continuing the Salamanca project developed by the Archaeological Studies and Research Laboratory at the Federal University of Santa Maria, which aims to recover and enhance the archaeological heritage of the city. Aspects of material culture are presented throughout this work which focused on the analysis of chinaware, regarding its consumption meaning. Although the primary purpose of either contemporary or pre-colonial ceramic artifacts is to maintain either solid or liquid waste, they can be endowed with a symbolic characteristic which transcends their original functionality. Would the chinawares have only a functional character? Were they status registering devices? What meaning would they have for those who used them? From the study of the chinawares, we tried to interpret part of the everyday life of that site inhabitants.